The impact of culture on language and thinking - بدران لؤي (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The cases of language, thinking and culture are still gaining a great attention by students on the levels of vocabulary, relativity and differences. Also, language has a crucial role in culture and communications. And there is a massive role of which culture affects language; as Crumch sees that culture also affects "the usage of printed language as it gives the printed language a social perspective, and cultural traditions give the text a passport to reach the readers easily because the most impoertant thing is not what we write, or to whom we write or the circumstances we write in; but the most important thing is the type of the text we are providing…allowed by the society’s cultural traditions that are found within the language, or those we call forms of interaction or interpretation that are parts of texts that culture exposes to the language users." By this, the effect between language and culture is equal and each one of them has an impact on the other. This research has three parts; the first discusses the meaning and the concept extensively, the second part discusses the reasons behind the formation of language, culture and thinking, while the last part discusses the relationship between language and thinking, and language and culture. Key words: language, culture, thinking